The cultural impact in theatrical practice to promote teaching / learning of FLE. - KHARKHACHE, Souhila; ladjel, djelloul; kharchi, lakhdar (Journal of Social Sciences and Humanities, 2021)
The integration of the term culture is nowadays established in the teaching and learning processes of the foreign languages and in FLE particularly. In order to achieve this purpose, theater seems to be one of the best teaching/learning tools and supports which could foster the language acquisition by providing a playful atmosphere which is full of fun and entertainment. Along this line of thought, the present investigation aims first at examining the school textbook in order to evaluate the integration of the cultural background and second emphasizes on the impact of the theater which directly targets the language and makes it possible to live it.